Hydraulic fracture productivity performance in tight gas sands, a numerical simulation approach - Ostojic, Jakov (Curtin University, 2013)
Hydraulically fractured tight gas reservoirs are one of the most common unconventional sources being produced today, and look to be a regular source of gas in the future. Tight gas sands by definition have extremely low permeability and porosity, and are most often uneconomical to produce without the aid of some form of reservoir stimulation. Hydraulic fracturing is one of the most common forms of commercially extracting gas from tight gas sands and is becoming increasingly popular in America, Canada and the rest of the world, with some projects in Australia.Along with the low productivity, tight gas sands are faced with other additional challenges if compared to conventional reservoirs, such as near wellbore damage due to water blocking, mechanical damage, fluid invasion and wellbore breakouts. In addition, inaccuracy of conventional build-up and draw-down well test results is common. This is primarily due to the increased time required for transient flow in tight gas sands to reach pseudo-steady state condition. To increase accuracy, well tests for tight gas reservoirs must be run for longer periods of time which is in most cases not economically viable. This leads to the need for accurate simulation of tight gas reservoir well tests or a reduction in analysis time.The primary aim of this research project is to use early time well test and production data to determine insights into hydraulic fracture productivity performance. The work is presented with reference to two published peer-reviewed papers published as lead author and one peer-reviewed paper published as co-author. The two main methods of analysis used will be Horner plot and a semi-log plot of production rate vs. log-time. Sensitivity analysis on fracture number, size and orientation with respect to the wellbore are conducted.The production and pressure buildup data is generated using commercial 3-D reservoir simulation software, Eclipse. A box model with generic tight gas properties is created with realistic hydraulic fracture and well completion simulated. Data is either compared to an unfractured tight gas sand model, or to a model with different number of fractures but comparable overall fracture volume.